2017
DOI: 10.1038/s41598-017-17813-0
|View full text |Cite
|
Sign up to set email alerts
|

Transit and integration of extracellular mitochondria in human heart cells

Abstract: Tissue ischemia adversely affects the function of mitochondria, which results in impairment of oxidative phosphorylation and compromised recovery of the affected organ. The impact of ischemia on mitochondrial function has been extensively studied in the heart because of the morbidity and mortality associated with injury to this organ. As conventional methods to preserve cardiac cell viability and contractile function following ischemia are limited in their efficacy, we developed a unique approach to protect th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 50 publications
3
92
0
1
Order By: Relevance
“…They observed that, by simple co-incubation, chloramphenicol-(CAP s ) and efrapeptin-(EF s ) sensitive mammalian cells were able to incorporate mitochondria, purified beforehand from CAP r and EF r resistant cells [97]. Ever since, many cells have been reported to undergo mitochondrial transformation [55,[98][99][100][101][102]. This process is believed to occur via macropinocytosis.…”
Section: Transfer Of Free Mitochondriamentioning
confidence: 99%
“…They observed that, by simple co-incubation, chloramphenicol-(CAP s ) and efrapeptin-(EF s ) sensitive mammalian cells were able to incorporate mitochondria, purified beforehand from CAP r and EF r resistant cells [97]. Ever since, many cells have been reported to undergo mitochondrial transformation [55,[98][99][100][101][102]. This process is believed to occur via macropinocytosis.…”
Section: Transfer Of Free Mitochondriamentioning
confidence: 99%
“…Mitochondrial number, viability and purity are assessed in all mitochondrial preparations using an aliquot of the isolated mitochondria. Mitochondrial number and size are determined by particle size analysis and light microscopy using fluorescent mitochondrial specific labels MitoTracker Red CMXRos (Invitrogen, Carlsbad, CA, USA) which labels only viable mitochondria maintaining membrane potential followed by MitoTracker Green FM, which labels all mitochondria independent of membrane potential and then by transmission electron microscopy (15)(16)(17)19). Mitochondrial viability is determined by oxygen consumption rate using a Clark-type electrode and fluorescent probe analysis (15,17,21,22).…”
Section: Mitochondrial Isolationmentioning
confidence: 99%
“…These cytokines are associated with reduced cardiomyocyte apoptosis and enhanced functional cardiac recovery and cardiac remodeling independent of cardiac myocyte regeneration (16). The mitochondria are rapidly internalized (2.5-60 min) into myocardial cells by actin-dependent endocytosis where they up-regulate cellular function and repair damaged mitochondrial DNA (17,19). The transplanted, mitochondria maintain viability and function for at least 28 days and have no pro-arrhythmic inflammatory, immune or auto-immune response (16,18,20).…”
Section: Introductionmentioning
confidence: 99%
“…The entry mechanism of mitochondria into cells would be associated with actin-mediated endocytosis because actin polymerization inhibitors can prevent the internalization of mitochondria by cells [34,35]. After the mitochondria enter cells, they are transported to lysosomes, then majority of the mitochondria can escape from the lysosomes and play roles in cytosol [36]. Moreover, it has been identified that exogenous mitochondria can promote neurogenesis, and activate the expression of brain-derived neurotrophic factor (BDNF) in the reported articles [7,37,38].…”
Section: Discussionmentioning
confidence: 99%